Telaah Sosiologis atas Fenomena Judi Online dan Upaya Pemberantasannya Perspektif Maqashid Syariah - Fajri, Ahmad Khairul; Kurniati, Kurniati; Mustafa, Zulhas’ari (Shar-E : Jurnal Kajian Ekonomi Hukum Syariah, 2025)
The phenomenon of online gambling in Indonesia has experienced a significant increase in line with the advancement of digital technology, leading to various social, economic, and moral impacts within society. From a sociological perspective, online gambling is not only regarded as a legal violation but also as a social symptom that reflects weak social control, a crisis of values, and economic disparities. It has triggered multiple problems such as rising debt, divorce, criminality, and even structural poverty. From the perspective of Maqashid Syariah—which encompasses the five essential objectives of preserving religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-‘aql), lineage (hifz al-nasl), and wealth (hifz al-mal)—online gambling is clearly in contradiction with Islamic law, as it destroys wealth, intellect, and family stability. Efforts to eradicate it cannot rely solely on legal measures but must also be reinforced through moral education, the strengthening of community-based economic resilience, and integrated technological supervision. The Maqashid Syariah approach provides a normative and strategic foundation to assess and comprehensively address online gambling, not only for legal compliance but also for the pursuit of sustainable social well-being. Therefore, the integration of state policy and religious values becomes the key to effectively responding to this phenomenon.